Isolation and growth characterization of novel full length and deletion mutant human MERS-CoV strains from clinical specimens collected during 2015. (8th October 2019) - Tamin, Azaibi; Queen, Krista; Paden, Clinton R.; Lu, Xiaoyan; Andres, Erica; Sakthivel, Senthilkumar K.; Li, Yan; Tao, Ying; Zhang, Jing; Kamili, Shifaq; Assiri, Abdullah M.; Alshareef, Ali; et al.
Abstract : Middle East respiratory syndrome (MERS) is a viral respiratory illness first reported in Saudi Arabia in September 2012 caused by the human coronavirus (CoV), MERS-CoV. Using full-genome sequencing and phylogenetic analysis, scientists have identified three clades and multiple lineages of MERS-CoV in humans and the zoonotic host, dromedary camels. In this study, we have characterized eight MERS-CoV isolates collected from patients in Saudi Arabia in 2015. We have performed full-genome sequencing on the viral isolates, and compared them to the corresponding clinical specimens. All isolates were clade B, lineages 4 and 5. Three of the isolates carry deletions located on three independent regions of the genome in the 5′UTR, ORF1a and ORF3. All novel MERS-CoV strains replicated efficiently in Vero and Huh7 cells. Viruses with deletions in the 5′UTR and ORF1a exhibited impaired viral release in Vero cells. These data emphasize the plasticity of the MERS-CoV genome during human infection.